The Water Quality Monitoring Assistance At Ngesong Source - Samin, Samin; Adibah, Amalia Nur; Darmawan, Azhar Adi (OMNICODE Journal (Omnicompetence Community Developement Journal), 2024)
Maintaining the environment is everyone's obligation; it is a gift from God and must be maintained so that our families are free from disease. Maintaining the environment can be started by using clean water as a daily source. The service is located at Sumber Ngesong, and according to information, the water quality has been monitored for about 5 years. Because water from this source is always used by residents of Punten Village and its surroundings, it is very important to continue monitoring to ensure that the water quality remains good. Therefore, to monitor the water quality in question, this service accompanies parties who have related disciplines. To test the water quality physically and biologically, water samples were taken. The results of laboratory tests showed that the water did not contain potentially dangerous parameters, including coli bacteria. Thus, the water is still suitable for consumption and can be used as raw water. However, the service team recommends that it be processed first, such as boiling.